Trunk sway response to consecutive slip perturbations between subjects with and without recurrent low back pain. (February 2018) - Sung, Paul S.; Danial, Pamela
Abstract: Background: Trunk sway responses following perturbations are critical to develop adequate prevention strategies. It is unclear how postural responses with a handheld task can validly be transferred to treadmill-induced slip perturbations in subjects with recurrent low back pain (LBP). Objective: To compare trunk sway angle, velocity, and reaction time following treadmill-induced perturbations while subjects with and without LBP held a tray. Design: Cross-sectional study. Methods: There were 30 subjects with LBP and 50 control subjects who participated in the study. Each participant stood on the treadmill while he/she held a tray to produce a functional task. Three levels of consecutive slips were introduced based on the specific duration, velocity, and displacement. Results: The trunk extension angle was significantly different (F = 4.22, p = 0.04) and demonstrated a significant interaction with groups and levels of perturbation (F = 6.83, p = 0.01). However, the reaction time was not significantly different based on the levels of perturbation (F = 0.43, p = 0.51). The LBP group increased trunk extension only at level 1 slip perturbation (t = 2.86, p = 0.005). Conclusion: The increased trunk extension following the first perturbation indicated a delay in adjusting trunk stability in the LBP group. However, there was no group difference with higher magnitudes of perturbations. These results indicated that the LBP group was able to minimize trunk sway with higher perturbations following the first perturbation. Highlights: Trunk extension increased in the LBP group only at the level 1 slip perturbation. Trunk sway reaction time was not different between groups. The trunk sway velocity was not sensitive enough to demonstrate a group difference. The LBP group adjusted trunk sway angles with higher levels of perturbation. This perturbation reaction might be applied for rehabilitation strategies.